THE CONCEPT GUERRA IN SPANISH INTERNET DISCOURSE - Rybalka , Oleksandra (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is devoted to the study of lexical means through which the concepts are verbalized. The author gives a definition of such terms as “concept” and “conceptual sphere” with an emphasis on their complex structure providing those that are most relevant in the research. It was determined that the lexical and semantic as well as nominative fields of concepts are in the constant process of expansion, which is facilitated by the Internet discourse. The last mentioned is characterized by immediate transmission of current events, thus it enables the verbalization of concepts which are of considerable interest to the members of the community in a certain period of time. It was shown that in mass media discourse new concepts are constantly appearing, but also the existing ones are acquiring new meanings and connotations. Proceeding from the fact that the language can serve to create manipulative, untrue and propaganda information, it was determined that the study of the concept “war” is particularly relevant. The article considers the lexical means, by which the actualization of the concept GUERRA takes place in mass-media discourse, which include the lexeme “guerra” itself and its use with attributive adjectives as well as the synonyms of the lexeme “guerra”. The both above mentioned are also used with the verbs that have different semantic features. Personal contribution made by the author: in the process of researching the lexical means of realization of the concept GUERRA in the texts of Spanish online newspaper El Español the frame structure was created. The frame illustrates the actualization of the concept and highlights the connection of the concept GUERRA with the concept CRIMEN. ____________ References: • Blyznjuk, R., Skidchenko, R. O. «Asociatyvne pole konceptu vijna u svidomosti ukrai’ns’koi’ molodi.» Zakarpats’ki filologichni studii’ 23 (1) (2022): 18–23. • Bogomolec’-Barash, M. Naprjamy kognityvnyh doslidzhen’ v Ukrai’ni: referat (Kyi’v: KNU im. Tarasa Shevchenka, 2022),13. • Broslavs’ka, Ja. «Koncept vijna v anglomovnij kartyni svitu: dokonceptual’ni osnovy.» Visnyk Harkivs’kogo nacional’nogo universytetu imeni V. N. Karazina, Serija: Romano-germans’ka filologija. Metodyka vykladannja inozemnyh mov 1051 (73) (2013): 46–51. • Dacyshyn, P. «Atrybutyvna spoluchuvanist’ konceptu gidnist’ u suchasnomu ukrai’ns’komu Internet-dyskursi.» Visnyk Nacional’nogo universytetu «L’vivs’ka politehnika», Serija: Zhurnalists’ki nauky 3 (L’viv: Vyd-vo L’vivs’koi’ politehniky, 2019): 142–149. • Pryhod’ko, M. Koncepty i konceptosystemy v kognityvno-dyskursyvnij paradygmi lingvistyky (Zaporizhzhja: Prem’jer, 2008), 332. • Shevchenko, S., Morozova, I. I., Shevchenko, V. O. «Nominacii’ agresii’ Rosii’ proty Ukrai’ny v anglomovnyh media: kognityvno-pragmatychnyj analiz.» Visnyk HNU imeni V. N. Karazina, Serija: Inozemna filologija. Metodyka vykladannja inozemnyh mov 95 (2022): 70–77. • Shevchenko, M. «Reprezentacija konceptu WAR v anglomovnij lingvokul’turi.» Naukovi zapysky, Serija: Filologichni nauky 193 (2021): 133–139. • Barnes, «Language, War and Peace: An Overview.» Language Matters: Studies in the Languages of Africa34 (1) (2003): 3–12. • Lakoff, , Johnson, M. Metaphors we live by (University of Chicago Press, 2003), 276. • Melnyk, , Holoiukh, L., Kalishchuk, D., Levchuk, I. «Verbal Markers of the Concept of Peace: Psycholinguistic and Lexical Analyses.» East European Journal of Psycholinguistics7 (2) (2020): 214–230. • Snyders, R. «Mechologic and ecologic: Blueprints for war and peace.» Language Matters: Studies in the Languages of Africa34 (1) (2003): 80–85. • Guerra Rusia-Ucrania, https://www.elespanol.com/temas/guerra_rusia_ucrania/